Does Inflation Matter The Influence of Perceived Price Changes on Well-being - Below, Łukasz (Central European Journal of Economic Modelling and Econometrics, 2024)
We confirm the inflation and well-being correlation scheme while filling the gap in the literature and estimating the effects of inflation perception on wellbeing. We discover the significant heterogeneity in attitudes toward inflation and inflation perception among European countries. While the inflation perception influence on well-being in Eastern Europe is higher than the influence of HICP, for Western Europe, it is the opposite. Both groups differ in terms of the marginal rate of substitution between inflation and unemployment – the effects of higher unemployment are more severe in comparison to the influence of inflation in Western Europe.